2015
DOI: 10.1371/journal.pone.0123608
|View full text |Cite
|
Sign up to set email alerts
|

Of PCOS Symptoms, Hirsutism Has the Most Significant Impact on the Quality of Life of Iranian Women

Abstract: IntroductionPolycystic ovary syndrome is a common endocrine disorder affecting women both physically and psychologically and can lead to a poor quality of life compared to their normal counterparts. The aim of the present study was to assess the impact of various clinical features of polycystic ovary syndrome on the health-related quality of life of Iranian women diagnosed with this syndrome.Materials and MethodsA total of 796 women diagnosed with polycystic ovary syndrome, aged 15–49 years, completed the ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 39 publications
(65 reference statements)
5
45
0
4
Order By: Relevance
“…This adaptation have been introduced before by Bishop et al,50 who presented a quality of life-based model of psychosocial adaptation to chronic illness and disability. In line with results of previous studies,4,7,13,51 this study also concluded that obesity and hirsutism are two important factors for worsening QoL and its domains in patients with PCOS.This study showed worsening QoL with increasing menstrual intervals; this relationship was significant only for the fertility domain of QoL. The present study, similar to previous studies, showed significant associations between QoL and clinical manifestations of PCOS.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This adaptation have been introduced before by Bishop et al,50 who presented a quality of life-based model of psychosocial adaptation to chronic illness and disability. In line with results of previous studies,4,7,13,51 this study also concluded that obesity and hirsutism are two important factors for worsening QoL and its domains in patients with PCOS.This study showed worsening QoL with increasing menstrual intervals; this relationship was significant only for the fertility domain of QoL. The present study, similar to previous studies, showed significant associations between QoL and clinical manifestations of PCOS.…”
supporting
confidence: 92%
“…2 PCOS is also associated with an increased risk of obesity, hyperinsulinemia, insulin resistance and long-term health implications, including type 2 diabetes mellitus and cardiovascular diseases 3 ; these signs and complications can lead to psychosocial and emotional disturbances and a decrease in their quality of life (QoL). 11 While the relationship of clinical characteristics of PCOS with QoL is well documented, [12][13][14] it is unclear that whether biochemical aspects of PCOS can independently influence QoL in these patients. Given the nature of these symptoms, it is to be expected that PCOS can have a negative impact on feminine identity of patients that leads to worsening different domains of QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Hirsutism was seen in 12% of the girls.About 10% of Caucasian females have symptoms of hirsutism 15 .There is an increase in 5 alpha reductase activity in hair follicles of hirsute females 15. Khomani et al 16 in their study found that hirsutism had the strongest impact on the health related quality of life measures in Iranian women diagnosed with PCOS. Ekback et al 17 evaluated the experiences of women with hirsutism and reported that a majority of these women had negative body image and considered themselves ugly and unattractive, which lowered their self esteem and limited their social interaction.…”
Section: Resultsmentioning
confidence: 97%
“…Most women (91.7%) meeting the criteria for PCOS had at least one skin finding, with higher burden of acne, hirsutism, and acanthosis nigricans (AN) than women who did not meet the criteria [6]. In the present study, following the recommended diet for 12 weeks has significantly reduced acne and hirsutism scores and maintained that effect for another 12 weeks, which may be beneficial for improving all the other symptoms related to it, as beside all the previous mentioned symptoms, PCOS women may display several psychological disorders such as depression, anxiety, marital and social problems, which aggravate the psychological impact of hirsutism as, not only is hirsutism itself a major concern for women diagnosed with PCOS, but the time and effort spent eliminating it aggravates the distress [7], hence emerge the importance of measuring hirsutism because hirsutism score is the main predictor of psychological distress [34] and can significantly predict reduction of body hair, emotions, menstrual problems, weight and infertility problems, in their order of severity [7] Hirsutism was also associated with a higher mean HOMA-IR, body mass index, and triglycerides level, as well as a lower HDL-C level [6]. Although acne is not a reliable marker of hyperandrogenism, Androgens are important in the development of acne and its prevalence is high among patients who meet PCOS diagnosis [6].…”
Section: Discussionmentioning
confidence: 98%
“…As the sense of self-consciousness is originated from the concept "ideal hair pattern" known inside the patients' social and cultural environment [4]. Khomami et al, mentioned that in PCOS diagnosed Iranian women, hirsutism has the strongest impact on the health-related quality of life [7]. Acne is the most common disease of the skin with a prevalence of 15% in all age groups.…”
mentioning
confidence: 99%